The Cults of the Epic Heroes and the Evidence of Epic Poetry - Damon, P. (1974)
Responses by M. N. Nagler, W. J. Heimpel, A. D. Kilmer, J. E. Fontenrose, A. Henrichs: 10-15.33; the Gilgamesh tradition.